Challenges for popular feminism: Urban interventions in Pedregal de Santo Domingo, Mexico - Socorro Pérez-Rincón (Íconos)
This article reviews a theoretical and practical journey through different aspects of urban intervention and collaborative design in the Pedregal de Santo Domingo neighborhood, using as methodology a research circuit and participatory action (IAP). This text will be used as a pedagogical resource for urban planning, architecture, and students in other related disciplines interested in urban transformation. The first part of the article identifies positions, scales, and theoretical bases to develop a critical and ethical proposal in relation to urban planning, including feminism’s contributions, particularly those of grassroots feminism. This community perspective radically transforms ways of participating and habitat improvement. The second part contains an account of the experience of the Casa de las Mujeres "Ifigenia Martínez" project, collaborative cartographic analysis, and results from the workshops conducted with neighborhood women. Finally, the article includes a reflection on community experiences and challenges of urban planning and research, focusing on growing gender inequalities. It is concluded that urban practices geared towards the ethical dimension of planning and the application of feminist methodologies contribute to designing new spaces for coexistence and addressing insecurity and violence experienced by women.